PENERAPAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD NEGERI 104209 SAENTIS - Sorta Simanjuntak; Wesly Silalahi; Winda Syafitri (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to improve student learning outcomes by applying the Word Square learning model. This type of research is Classroom Action Research (CAR). This research was conducted at SD Negeri 104209 Saentis. The subjects are students of class IV B with a total of 29 students, while the object of this research is the improvement of student learning outcomes. Data collection techniques used are tests and observations. The results of the pretest data analysis showed that from 29 students who completed as many as 8 people (27.50%) by exceeding the KKM = 70 and 21 students (72.41%) had not completed, with a class average of 53.10. Furthermore, the results of data analysis in the first cycle showed that of the 29 students who completed as many as 18 people (62.07%) and 11 people (37.93%) who had not completed, with an average grade of 70.86. In the second cycle, there was an increase in student learning completeness, namely from 29 students, 25 (86.21%) were completed and 4 (13.79%) were not completed, with the average grade of the class increasing to 80.69. The results of observations of teacher activities in the first cycle of the first meeting were 81.67% and at the second meeting of the second cycle it increased again to 93.33%. Based on the findings from the research, it can be concluded that the application of the Word Square model can improve student learning outcomes on the theme 8 My Living Area in class IV SD Negeri 104209 Saentis 2018/2019 academic year. Keywords: Word Square and Student Learning Outcomes